Teachers' Perceptions and Challenges in Implementing Differentiated Learning in Kurikulum Merdeka - Sianturi, Betty (UIR Press, 2025)
This study investigates teachers' perceptions of implementing differentiated learning in the context of the Kurikulum Merdeka, focusing on how it impacts teaching and learning. Through a qualitative case study approach, the research involved in-depth interviews with five teachers from Balikpapan City, East Kalimantan, who have between three to twenty-two years of teaching experience. The study explores teachers' preparedness to apply differentiated learning, their beliefs regarding its benefits, and the challenges they face in its implementation. While teachers recognize that differentiated learning fosters student engagement and accommodates diverse learning needs, they also encounter significant obstacles such as limited resources, time constraints, and the complexity of managing diverse student abilities and moods. Despite these difficulties, teachers commit to overcoming challenges by adopting creative strategies and continuous adaptation. The findings emphasize the need for institutional support, including training and resources, to enable teachers to implement differentiated learning effectively. This research contributes to how differentiated instruction can be more successfully integrated into classrooms under the Kurikulum Merdeka.